2013
DOI: 10.1093/ehjci/jet162
|View full text |Cite
|
Sign up to set email alerts
|

Neointimal patterns obtained by optical coherence tomography correlate with specific histological components and neointimal proliferation in a swine model of restenosis

Abstract: The optical characteristics of neointimal formation seen in OCT properly correlated with the presence of several histological findings involved in stent healing. The biological implications of these findings in clinical outcomes require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 23 publications
5
40
2
Order By: Relevance
“…In addition, recent studies suggest that the different characteristics of neointimal tissue seen by OCT may correlate with clinical events such as late stent thrombosis. 20) Kim, et al 21) compared different OCT morphological characteristics with different in-stent neointimal tissue types analyzed by histology and found that the homogeneous pattern of neointimal formation appeared to correlate with less neointimal formation and more favorable vessel healing characteristics when compared with the other optical patterns; the heterogeneous pattern correlated more with the presence of fibrin deposits than the other patterns; the layered pattern correlated with the higher incidence of peri-strut inflammation, neovascularization, and external elastic lamina rupture, which might lead to a higher degree of neointimal proliferation. In a clinical study, Tanaka, et al 22) concluded that in DM patients, the heterogeneous pattern was observed with high frequency.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies suggest that the different characteristics of neointimal tissue seen by OCT may correlate with clinical events such as late stent thrombosis. 20) Kim, et al 21) compared different OCT morphological characteristics with different in-stent neointimal tissue types analyzed by histology and found that the homogeneous pattern of neointimal formation appeared to correlate with less neointimal formation and more favorable vessel healing characteristics when compared with the other optical patterns; the heterogeneous pattern correlated more with the presence of fibrin deposits than the other patterns; the layered pattern correlated with the higher incidence of peri-strut inflammation, neovascularization, and external elastic lamina rupture, which might lead to a higher degree of neointimal proliferation. In a clinical study, Tanaka, et al 22) concluded that in DM patients, the heterogeneous pattern was observed with high frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the extracellular matrix increases and the number of smooth muscle cells decreases [14]. This condition develops into neointimal hyperplasia, which eventually causes ISR [15].…”
Section: Discussionmentioning
confidence: 99%
“…The length of an arc of lipid and calcium that occupied the vessel wall circumference was measured and expressed in degrees. 16, 17 The maximum lipid arc and calcium arc were measured. The thickness of the fibrous cap that covered the lipid core was measured in the thinnest part of a signal-rich zone that separated the lipid content from the vessel lumen (µm).…”
Section: Oct Analysismentioning
confidence: 99%